THE CORRELATION OF SCIENTIFIC ARGUMENTATION AND CRITICAL THINKING ON GLOBAL WARMING MATERIALS IN SMAN 19 SURABAYA - RACHMATYA, RENNY; SUPRAPTO, NADI (Inovasi Pendidikan Fisika, 2020)
Argumentation is a the process of preparing for a formal statement that is accompanied by evidence and logical reasons. This study aims to analyze the effect of scientific argumentation skills on critical thinking skills. The research subjects used were 11th-grade students in 19 Senior High School, Surabaya. This study used an experimental design with quantitative descriptive 100 subjects of three classes. The question given is included in the topic of global warming. The research subjects were given ten questions related to scientific literacy and critical thinking questions. These ten questions must imply answered by giving logical reasons to support their answers. Each student?s answers will be adjusted to the Toulmin?s Argumentation Pattern assessment guidelines that have been adapted. The results of this study indicated that students scientific argumentation in level 2 and student?s critical thinking in a moderate level. On average students provide good claims and evidence. In Pearsons correlation test, scientific argumentation skills on critical thinking skills have a great relationship. Knowing the level of student?s intial ability in the arguments related to critical thinking, it can be prepared learning models that can provide to supporting influence in learning activities. Keywords: Argumentation, critical thinking, and global warming